Towards a Blockchain-Based Multi-UAV Surveillance System - Santos De Campos, Mário Gabriel; Chanel, Caroline P. C.; Chauffaut, Corentin; Lacan, Jérôme (Frontiers in Robotics and AI, 2021)
This paper describes a blockchain-based multi-UAV surveillance framework that enables UAVs coordination and financial exchange between system users. The system’s objective is to allow a set of Points-Of-Interest (POI) to be surveyed by a set of autonomous UAVs that cooperate to minimize the time between successive visits while exhibiting unpredictable behavior to prevent external agents from learning their movements. The system can be seen as a marketplace where the UAVs are the service providers and the POIs are the service seekers. This concept is based on a blockchain embedded on the UAVs and on some nodes on the ground which has two main functionalities. The first one is to plan each UAV’s route through an efficient and computationally cheap game-theoretic decision algorithm implemented into a smart contract. The second one is to allow financial transactions between the system and its users, where the POIs subscribe to surveillance services by buying tokens. Conversely, the system pays the UAVs in tokens for the provided services. The first benchmarking experiments show: that the IOTA blockchain is a potential blockchain candidate to be integrated in UAVs embedded system; and, that the chosen decentralized decision-making coordination strategy is efficient enough to fill the mission requirements while being computationally light.